1996
DOI: 10.1002/(sici)1520-6769(199603)18:2<87::aid-nrc144>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethanolamine (ETN) Administration on etn and choline (CH) levels in plasma, brain extracellular fluid (ECF) and brain tissue, and on brain phospholipid levels in rats: An in vivo study

Abstract: The sources and fates of brain ethanolamine (Etn) are poorly known and the effects of its administration have not been investigated, even though cortical levels are known to be reduced in certain neurodegenerative diseases. We studied the effect of different Etn doses (10−3, 5 × 10−3 and 10−2 mol/kg, i. p.) on its and choline's (Ch) levels in arterial plasma and brain extracellular fluid (ECF) of awake rats. We also studied its effects on brain levels of Etn, Ch, and their respective major phospholipids. Etn a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…One biopsy had choline concentrations approximately five times those of the other two, possibly indicating the occurrence of ischemia in the brain tissue from which the biopsy was taken, since ischemia leads to a rapid rise in tissue free choline concentration (42). However, in two biopsies, tissue choline concentration was approximately 40 µM, a value comparable to that found in rodent brain (30-60 µM (23,24). Thus, under normal conditions, human brain choline kinase may be viewed as a single enzyme half maximally active at choline concentrations of approximately 20 µM (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…One biopsy had choline concentrations approximately five times those of the other two, possibly indicating the occurrence of ischemia in the brain tissue from which the biopsy was taken, since ischemia leads to a rapid rise in tissue free choline concentration (42). However, in two biopsies, tissue choline concentration was approximately 40 µM, a value comparable to that found in rodent brain (30-60 µM (23,24). Thus, under normal conditions, human brain choline kinase may be viewed as a single enzyme half maximally active at choline concentrations of approximately 20 µM (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, Etn may affect brain myoIns levels through indirect mechanisms. Specifically, we know that Etn administration can cause alterations in phospholipid concentrations (12) and choline concentrations (22) in rat brain. How myo-Ins and Etn interact within the brain is unknown; however, there seems to be a relationship between the two substances when in combination.…”
Section: Effects On Myo-ins Concentrationsmentioning
confidence: 98%
“…In another study, it was observed [34] that high dietary fat for eight weeks decreased the PEA levels in the small intestine of mice, but not after 14 weeks of high-fat diet. To date, no data exists regarding the effect of dietary ethanolamine on PEA or other NAE tissue levels, although it has been seen that the contribution of an ethanolamine supplement increases the levels in the brain of phosphatidylethanolamine and also in liver microsomes [35,36]…”
Section: Diet Modify Pea Levelsmentioning
confidence: 99%